Can the fluctuations of motion be used to estimate the performance of kayak paddlers?. (20th May 2016) - Vadai, Gergely; Gingl, Zoltán
Abstract: Today many compact and efficient on-water data acquisition units help modern coaching by measuring and analyzing various inertial signals during kayaking. One of the most challenging problems is how these signals can be used to estimate performance and to develop the technique. Recently we have introduced indicators based on the fluctuations of the inertial signals as promising additions to the existing parameters. In this work we report on our more detailed analysis, compare new indicators, and discuss the possible advantages of the applied methods. Our primary aim is to draw attention to several exciting and inspiring open problems and to initiate further research even in several related multidisciplinary fields. More detailed information can be found on the dedicated webpage, www.noise.inf.u-szeged.hu/kayak .